Becoming a leader coach a step by step guide to developing your people - Naude, Johan (US Center for Creative Leadership, 2014)
As a leader, you have different roles to play with your direct reports. One of them is to manage their day-to-day performance. Another is to support their development so they can continue to deliver top performance. Most leaders are comfortable with and effective in the first role. However, many leaders are less clear about the role of developing their direct reports, particularly coaching for development. This guidebook provides an introduction to leader-coaching, including a structure and a set of guidelines to conduct effective formal and informal coaching conversations with your direct reports.
Keywords: Leadership